2018
DOI: 10.1186/s12936-018-2597-6
|View full text |Cite
|
Sign up to set email alerts
|

Origins and spread of novel genetic variants of sulfadoxine–pyrimethamine resistance in Plasmodium falciparum isolates in Indonesia

Abstract: BackgroundWhile malaria incidence in Indonesia has decreased threefold in the last decade, more than 200,000 cases were reported in 2016. Different endemicity of Plasmodium falciparum malaria among several islands in Indonesia has been recognized and two unique mutations of P. falciparum dihydropteroate synthase (pfdhps) affecting sulfadoxine–pyrimethamine (SP) resistance were detected from the research of SP efficiency and genotype analysis in South Kalimantan. In this study, geographical distribution and ori… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 26 publications
(33 reference statements)
0
11
1
Order By: Relevance
“…Moderate level of resistance conferred by dhfr and dhps polymorphisms is typically found in West Africa with the absence of I164L polymorphism that is associated with very high-level SP resistance (up to 20 000-fold decrease in susceptibility in comparison with the wild type) [50]. I164L polymorphism have been variously reported in parts of East Africa [51], some parts of South Africa [52] and Asia [53]. There is dearth of information on why I164L mutation does not occur in Africa despite extensive drug pressure.…”
Section: Discussionmentioning
confidence: 99%
“…Moderate level of resistance conferred by dhfr and dhps polymorphisms is typically found in West Africa with the absence of I164L polymorphism that is associated with very high-level SP resistance (up to 20 000-fold decrease in susceptibility in comparison with the wild type) [50]. I164L polymorphism have been variously reported in parts of East Africa [51], some parts of South Africa [52] and Asia [53]. There is dearth of information on why I164L mutation does not occur in Africa despite extensive drug pressure.…”
Section: Discussionmentioning
confidence: 99%
“…e present study reports the prevalence of Pfdhfr SNPs at codons N51I, C59R, and S108N and codons S436A/F, A437G, and K540E of Pfdhps and discusses the implications on malaria prophylactic strategies in Maiduguri, Northeast Nigeria. Pfdhfr and Pfdhps genes have been widely used as biomarkers for monitoring pyrimethamine and sulfadoxine resistance, respectively [23,24,26,27,36]. e detection of Pfdhfr mutations in the present study is an indication of circulating pyrimethamine-resistant P. falciparum strains in the region.…”
Section: Discussionmentioning
confidence: 77%
“…Previous studies have reported SP resistance in Nigeria [20][21][22] and other countries where strategies are deployed [23][24][25][26]; thus, the need for periodic monitoring of SP efficacy to ensure early detection of drug resistance. Single nucleotide polymorphisms (SNPs) in P. falciparum dihydrofolate reductase (Pfdhfr) and P. falciparum dihydropteroate synthase (Pfdhps) are strong predictors of SP resistance [20,23,26,27]. Pyrimethamine resistance is associated with point mutations at codons N51I, C59R, S108N, and I164L of Pfdhfr [28], while sulfadoxine resistance is associated with point mutations at codons S436A/F, A437G, K540E, A581G, and A613S/T of Pfdhps [29].…”
Section: Introductionmentioning
confidence: 99%
“…S/P is also used in combination with amodiaquine for malaria chemoprevention [8]. However, there is emergence and wide spread resistant to S/P by Plasmodium parasites primarily P. falciparum [9]. This resistance has been attributed to point mutations in its target enzymes (dihydropteroate synthase and dihydrofolate reductase) which are involved in folate biosynthesis pathway [10].…”
Section: Introductionmentioning
confidence: 99%